Community health agents: strategies and consequences of their network of relationships and interactions - Gabriela Marcellino de Melo Lanzoni; Caroline Cechinel; Betina Hörner Schlindwein Meirelles (Universidade Federal do Ceará, 2014)
This study aimed to identify the strategies used by Community Health Agents on their relationships network and interactions to improve health care and its impact on a health center. The Grounded Theory was used as a methodological reference. Seventeen participants were interviewed between February and April 2009, among professionals and users of a health center in a city from southern Brazil. Freedom of communication, being the bond and promoting a connection between the community and the professionals were identified as strategies to strengthen the network of relationships and interactions of the Community Health Agents, creating as consequences good relationships between the staff and users and facilitating access to the health unit. One concludes that the Community Agent is a tool in the bond formation with significant potential to facilitate access to the services offered in Primary Health Care, starting from a complex web of relationships and interactions.